The Effects Of Ownership Structures And Specific Characteristics On The Capital Structures Of Idx-Listed Banks - Imas Maesaroh (Sains: Jurnal Manajemen dan Bisnis, 2018)
The present study observes the effects of ownership structures and specific characteristics on the capital structures of banks listed in Indonesia Stock Exchange (IDX). The author finds that the ownership structures and bank-specific characteristics (e.g., profitability, size and credit risk) do not have significant partial effect on the capital structures, while expense management does. This is consistent with a strand of previous studies including Haruman (2008), Yuke and Hadri (2005), Rista and Bambang (2011), Siringoringo (2012) and (Imas, et al., 2015).